FLT4/VEGFR3 and Milroy Disease: Novel Mutations, a Review of Published Variants and Database Update. Issue 1 (16th October 2012) - Gordon, Kristiana; Spiden, Sarah L.; Connell, Fiona C.; Brice, Glen; Cottrell, Sally; Short, John; Taylor, Rohan; Jeffery, Steve; Mortimer, Peter S.; Mansour, Sahar; Ostergaard, Pia
ABSTRACT Milroy disease (MD) is an autosomal dominantly inherited primary lymphedema. In 1998, the gene locus for MD was mapped to 5q35.3 and variants in the VEGFR3 (FLT4) gene, encoding vascular endothelial growth factor receptor 3 (VEGFR3), were identified as being responsible for the majority of MD cases. Several reports have since been published detailing pathogenic FLT4 mutations. To date, a total of 58 different variants in FLT4, 20 of which are unpublished, have been observed in 95 families with MD. A review of published mutations is presented in this update. Furthermore, the unpublished variants are presented including clinical data. Comparison of clinical features in patients and their families with the same mutations reveals incomplete penetrance and variable expression, making genotype–phenotype correlations difficult. Most mutations are missense, but a few deletions and one splicing variant have also been reported. Several animal models have confirmed the role of VEGFR3 in lymphangiogenesis and studies show mutant VEGFR3 receptors are not phosphorylated. Here, an MD patient with the same p.Ile1053Phe change as seen in the Chy mouse is presented for the first time. This finding confirms that this mouse lineage is an excellent model for MD. All the data reviewed here has been submitted to a database based on the Leiden Open (source) Variation Database (LOVD) and is accessible online at www.lovd.nl/flt4.